DOI: 10.3990/1.9789036544641
|View full text |Cite
|
Sign up to set email alerts
|

Crustal and upper mantle structure of Botswana

Abstract: I am deeply grateful to my teacher Dr. Amin Ismail. You are my geophysical teacher, all what I achieved return back to you. My deep gratitude goes to the staff members and my teaching assistant friends at Geology Department at Helwan University. Special thanks to Dr. Yahia Alqazaz, Dr. Al Ibiary, and Dr. Mostafa Gharib to faciliate my paper work and helping me extending my study leave to finish my PhD studies at ITC. Special thanks go to my relatives and friends back home in Egypt. You have been always there v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
33
0

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(40 citation statements)
references
References 126 publications
(299 reference statements)
7
33
0
Order By: Relevance
“…Figure 1). Along the Okavango Rift Zone in the north-western part of Botswana, z b is shallow ranging from 8 to 15 km, which coincides with the thermal perturbation of Okavango Rift (Leseane et al, 2015) and crustal thinning (Fadel et al, 2020). Toward the eastern part of Botswana, an intermediate Curie depth is estimated, which coincides with the Zimbabwe Craton and the old Magondi and Limpopo belts in this area.…”
Section: Curie Depth Compared With Magnetic and Geological Settingmentioning
confidence: 65%
See 2 more Smart Citations
“…Figure 1). Along the Okavango Rift Zone in the north-western part of Botswana, z b is shallow ranging from 8 to 15 km, which coincides with the thermal perturbation of Okavango Rift (Leseane et al, 2015) and crustal thinning (Fadel et al, 2020). Toward the eastern part of Botswana, an intermediate Curie depth is estimated, which coincides with the Zimbabwe Craton and the old Magondi and Limpopo belts in this area.…”
Section: Curie Depth Compared With Magnetic and Geological Settingmentioning
confidence: 65%
“…The Cenozoic era is characterized by the emergence of the initial rifts caused by the spread of the EARS to the South. Seismically active fault systems indicate that rifting is developing in the Okavango Rift Zone (ORZ) in northern Botswana (Schmitz & Bowring, 2003), with the EARS potentially extending to central Botswana as well (Fadel et al, 2020). The different tectonic domains with different tectonic history and different ages (varying from old Cratonic lithosphere, mobile belts, and Phanerozoic rifting to flood basalt volcanism combined with the plateau uplift and the terminus of the EARS) make southern Africa an open laboratory to study and map the variations of Curie depth along with different domains which have different tectonic history and current thermal states.…”
Section: 1029/2021gc010041mentioning
confidence: 99%
See 1 more Smart Citation
“…2.1 Ga Bushveld event within the Kaapvaal Craton (Figure 1). Karoo rifts and sedimentary basins developed across much of southern Africa during the breakup of Gondwana, and, today, rifting is ongoing within the East African Rift System, which extends to the southwest to the Okavango Rift Zone in northern Botswana and to the southeast into central Mozambique (Domingues et al, 2016;Fadel et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…6B). In addition, a relatively thin crust at the northeastern tip of Botswana in the Okavango Rift Zone is correlated with a low shear-wave velocity zone in the mantle (~150 km), which is interpreted as the East African Rift System (EARS) expression at northern Botswana (Fadel, 2018;Fadel et al, 2020). Fadel et al (2020) have suggested that the EARS expression at the northern tip of Botswana extends to the Incipient Okavango Rift region and the Moiyabana Epicentral regions through weak crustal zones.…”
Section: Implication To the 3rd April 2017 Botswana Earthquakementioning
confidence: 99%